#MisconstruedIdentitiesMustFall collective: Identity formation in the current South African context: A practical theological perspective - Brunsdon, Alfred R. (HTS teologiese studies, 2017)
In South Africa, 2015 was violently ushered out by several ‘must fall’ campaigns, of which the most prominent were the ‘fees’ and ‘Zuma must fall’ campaigns. These ‘must fall’ campaigns conveyed a new sense of urgency by the disgruntled masses towards certain institutions and individuals. Aligning with the ‘must fall’ analogy, the focus of this article is on combatting the notion of misconstrued identities in post-apartheid South Africa. Based on negative generalisation and perceptions of the ‘others’, misconstrued identities prohibit the formation of a collective identity that allows for peaceful co-existence. Consequently, the dynamics of collective identity formation and some of the possibilities for identity formation that reside within the Christian faith are investigated from a practical theological perspective. Given that a practical theological investigation takes both the context and theological reflection as points of departure, it is argued that it can contribute towards the dismantling of misconstrued identities to provide clues for the formation of a positive collective identity for South Africans.